A 45Gb/s Analog Multi-Tone Receiver Utilizing a 6-Tap MIMO-FFE in 22nm FDSOI - Jhoan Salinas; Hossein Shakiba; Ali Sheikholeslami (IEEE Open Journal of Circuits and Systems)
This paper describes an analog multi-tone receiver capable of processing three data streams running at 15 Gb/s, one in baseband and two in quadrature over carriers at 15GHz, achieving an aggregate rate of 45Gb/s over a single physical channel. The receiver maximizes bandwidth efficiency by using orthogonal sub-channels and avoids the need for analog to digital converters by incorporating a mixedsignal MIMO equalizer that can mitigate inter-symbol interference and inter-carrier interference. The system is designed and laid out in a 22nm FDSOI technology. Post-layout simulations are employed to verify the effectiveness of the proposed architecture, demonstrating a raw BER of 10−5 over a channel with an insertion loss of 14dB at 28GHz is achieved. The complete system has an energy efficiency of 6.6pJ/bit and occupies an active area of 0.29 mm2.